1995
DOI: 10.1002/j.1552-4604.1995.tb04024.x
|View full text |Cite
|
Sign up to set email alerts
|

Ceftizoxime Use In Trauma Celiotomy: Pharmacokinetics and Patient Outcomes

Abstract: Seriously injured patients undergo vigorous resuscitation upon arrival at the emergency department and through the immediate perioperative period. Although resuscitation leads to volume loading and fluid shifts, drug dosing and dosing intervals are often not altered to account for changes in total body volume or circulatory volume. To address this, a prospective study of pharmacokinetics of ceftizoxime in 53 injured adults who underwent emergency celiotomy was conducted. Further, the relationship between serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In fact, in a clinical trial on 53 patients undergoing emergency explorative laparotomy, Rosemurgy et al [31] found that signifi cant blood losses and subsequent abundant fl uid replacement caused serious reductions in antibiotic serum concentrations that are signifi cantly related to the appearance of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a clinical trial on 53 patients undergoing emergency explorative laparotomy, Rosemurgy et al [31] found that signifi cant blood losses and subsequent abundant fl uid replacement caused serious reductions in antibiotic serum concentrations that are signifi cantly related to the appearance of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%